The Genetic Germline Background of Single and Multiple Primary Melanomas - De Summa, Simona; Lasorella, Antonia; Strippoli, Sabino; Giudice, Giuseppe; Guida, Gabriella; Elia, Rossella; Nacchiero, Eleonora; Azzariti, Amalia; Silvestris, Nicola; Guida, Michele; Guida, Stefania; Tommasi, Stefania; et al. (Frontiers in Molecular Biosciences, 2021)
Background: Melanoma has a complex molecular background and multiple genes are involved in its development and progression. The advent of next generation sequencing platforms has enabled the evaluation of multiple genes at a time, thus unraveling new insights into the genetics of melanoma. We investigated a set of germline mutations able to discriminate the development of multiple primary melanomas (MPM) vs. single site primary melanomas (SPM) using a targeted next generation sequencing panel. Materials and Methods: A total of 39 patients, 20 with SPM and 19 with MPM, were enrolled in our study. Next generation analysis was carried out using a custom targeted sequencing panel that included 32 genes known to have a role in several carcinogenic pathways, such as those involved in DNA repair, pigmentation, regulation of kinases, cell cycle control and senescence. Results: We found a significant correlation between PIK3CA:p.I391M and MPMs, compared to SPMs, p = 0.031 and a trend for the association between CYP1B1: p.N453S and SPMs, compared to MPMs (p = 0.096). We also found that both subgroups shared a spectrum of 9 alterations in 8 genes (CYP1B1: p.N453S, BAP1: p.C39fs, PIK3CA: p.I391M, CDKAL1: c.1226_1227TG, POLE: p.V1161fs, OCA2: p.R419Q, OCA2: p.R305W, MC1R: p.V60L, MGMT: p.L115F), which suggested that these genes may play a role in melanoma development. Conclusions: In conclusion, despite the small cohort of patients, we found that germline mutations, such as those of PIK3CAand CYP1B1, might contribute to the differential development of SPM and MPM.